Religious Moderation and Religious Regulations: Harmony and Polarisation in the Dynamics of Society (Study of Sharia Regional Regulations in West Sumatra and Customary Village Regulations in Bali) - Wirman, Hardi Putra; Burhanuddin, Nunu; Nora, Vivi Yulia; Hendri, Novi; Syaban, Anwar (LPPM IAIN Kudus, 2026)
Regional regulations (peraturan daerah or Perda) with religious nuances, such as the Sharia regional regulation and the customary village (desa adat) regional regulation, are considered an effort to strengthen the community's moral values because they are rooted in local wisdom. However, it is often feared that it violates the principles of pluralism, justice, and the constitutional rights of citizens. This study explores the tangents, harmonization and polarisation of Religious Regulations in the context of religious moderation in West Sumatra and Bali. This study uses a qualitative approach, with data collected through interviews, participant observation, documentation, and literature review. The results of this study show that the intersection between religious moderation and the Religious Regulation lies in the goal of both to create a moral, harmonious and civilized society, the Religious Regulation seeks to translate religious values in public policy, while religious moderation functions as a balance maintainer so that religion-based policies remain inclusive and do not cause discrimination against other groups, This study also found that there is harmonisation and polarisation in the implementation of the religious regulation. Harmonization can be seen in the traditional philosophy, which serves as a guideline for formulating the religious regulation in the form of locality values that embody morals, ethics, and goodness. Meanwhile, polarisation is evident in the implementation of the religious regulation, which leads to discrimination against adherents of other religions, such as prohibitions on the establishment of houses of worship and on wearing clothing in accordance with specific religious teachings. This study recommends that the concept of religious moderation serve as a reference in the formulation of regional regulations that align with the principles of diversity and the state constitution. Religious moderation can serve as a bridge between local aspirations, religious values, and the principle of justice within the Indonesian state.